Subjektsegenskaper i förändring. Indefinita subjekt i fornsvenskt lagspråk - Sandelin Minna (Sweden, 2022)
In Old Swedish, the placement of the subject was tied to its function in the information structure of the clause: rhematic subjects, which are semantically indefinite and introduce a new referent to the text, were most often postverbal. The study analyses such subjects in Old Swedish legal language in relation to the order of constituents in the clause, the position of the clause in the text, and the structure of the subject. Three questions are posed: 1. What order of constituents is found in clauses with semantically indefinite subjects? 2. Do these clauses appear in initial, medial, or final position in paragraphs and subparagraphs? 3. What structure does a semantically indefinite subject have? The corpus consists of all main clauses (n=210) and subordinate clauses (n=28) with indefinite subjects in three sections of the Law of Uppland. An indefinite subject seldom (5.2%) appears in the preverbal position in main clauses, while this is common in subordinate clauses (71.4%). In over 93% of main clauses, the subject appears postverbally as the second or third constituent, but placement as the fourth constituent is rare. The main clauses are often verb-initial conditional clauses in which the preverbal position is not a possibility. The clauses tend to appear in initial or medial position in the text, in the introduction to a paragraph or a subparagraph. The subjects are mainly short, bare nouns, but they can also be combined with numerals, pronouns, or relative clauses.